“Home Garden” Household Food Security in Wat Bang Aoi Chang Community, Nonthaburi Province - Sangyuan, Natsiporn; Petyim, Tanasi Samphantharak; Phanumphai, Prapassara Naka (Area Based Development Research Journal, 2018)
The objectives of this research were to explore the benefits of home gardens and to study the guidelines for spatial conservation and development toward self-reliant community to enhance household food security in Wat Bang Aoi Chang community, Bang Si Thong sub-district, Bang Kruai district, Nonthaburi province. The researchers conducted participatory action research and collected data on home gardening, household and lifestyle of Wat Bang Aoi Chang community by using in-depth interviews and focus group discussions with key informants. The researchers also gathered data through action activities and community meetings. Data collected were arranged and then analyzed through content analysis, also the cause-effect relationships from participatory community activities were determined as a focus of the research. The participants proposed joint decisions on managerial guidelines and development policies associated with the conservation of self – reliant community particularly on the issue of food security. The results of this study indicated that the interest in the retainability of home garden was a common concern in Wat Bang Aoi Chang community because of urbanization trends and the changing lifestyle. The key informants jointly presented past and present home garden situations as well as defined home gardens as a household refrigerators. Houses with home gardens possessed an average land area of 3.2 rai. There were over 38 species of plants used in the household, which could reduce the household expense on food. Cost saving from consuming home garden produce was 7,096.63 baht per year per rai. The participants showed confidence in the qualities of their home garden produce in terms of cleanliness, safety, adequacy and nutritional value. In order to promote household food security and self-reliant community, the participants together proposed a managerial plan including 4 main actions: 1) Working on household accounts to show the hidden economical value of home garden produce consumed within each family; 2) Cultivating the awareness of the socio-cultural and economical values of home gardens among the local younger land owners; 3) Transferring local wisdoms and agricultural techniques to the next generations; and 4) Continuing and strengthening the work of home garden network in the community.